CREATIVE WEBSITE DESIGN IMPLEMENTATION FOR FOOTBALL CLUB SUPPORTERS IN INDONESIA - Istini, Syalis Ibnih Melati (Asosiasi Dosen Muda Indonesia, 2023)
The return of PSSI to implementing the league after the ban was lifted by FIFA, causing the public's enthusiasm for football to increase. Lots of creativity from the supporters who were present directly in the stadium which was amazing and really attractive and creative. Therefore, it is necessary to form an information media for a forum about the world of supporters in Indonesia and the results of the creativity of the supporters which are made with a web-based computer system. A website that contains information on how to dress supporters, the latest news on supporters and creativity from League I, League II and League III clubs. Making it easier for the public to get to know the various kinds of supporters in Indonesia and also see the creativity of supporters from various regions in expressing their support in the form of creative choreography. In making this website, information is obtained from reference books and internet media.Based on testing the website that has been made, it can be concluded that this Supporter Channel site has good quality for people who want to know about supporter information in Indonesia along with the diversity of creativity that exists with the website address